PERSPEKTIF DAN PERAN SOSIOLOGI EKONOMI DALAM PEMBANGUNAN EKONOMI MASYARAKAT (Forum Penelitian Agro Ekonomi, 2024)
Economic sociology is a sociological perspective that explains economic phenomena, mainly related to aspects of production, distribution, exchange, consumption of goods, services, and resources, aiming at improving people’s welfare. Contribution of the sub-discipline of economic sociology improves along with the various socio-economic problems in the society both in developed and developing countries where they try to improve people’s welfare through its development programs. Progress of economic sociology cannot be separated from the ideas of classical sociology and new thinking in economic sociology since 1980s. Economic sociology studies in Indonesia showed that most of the studies are directed toward on how the community alleviates poverty. Currently, economic sociology studies social capital, as well as structural problems, institutional and national economic systems associated with welfare. The said national economic system is in accordance with the country’s constitution. On the other hand, the impacts of national development are also the focus of the studies since the development policies have not been able to realize a welfare society and inclusiveness in national development. It is based on the construction of the welfare state model with the main indicator of relatively equal development.